EM CENA, O MOVIMENTO ESTUDANTIL ACADÊMICO NO MARANHÃO: 1930-1950 - Costa, Márcia Cordeiro (2009)
This investigation objective rescue and analyze the academic Student s Movement in Maranhão between 1930 and 1950, in a period that is organized and expanded the university teaching in our state, identifying the student s social and politics practices came back to structure this teaching. It focuses, in the initial, the study of Student s Press, adopting the methodology of the historic research and the documental analysis of the periodic press produced by the academics, localized in Biblioteca Pública Benedito Leite. The periodic analyzed are: Folha Acadêmica (1934), Esquerda (1934), Voz Universitária (1954), Universitário em Marcha (1955), Vigilância (1957), Movimento (1958) e Universitário (1958). It is emphasized the importance of this study made by a inside into the press to the History of Education (NOVÓA, 1993; CATANI E BASTOS, 1997), where the New Cultural History has made possible a theoretical subsidy to the research in this area (CERTEAU, 1994; CHARTIER, 1990). In this perspective, it accosts the representation of the research s fountains to a History of Education like a memory place (LE GOFF, 2003; NORA, 1993; BARBOSA, 1996). It emphasizes the contribution of this research to the reconstitution of History of the Education in the state of Maranhão, when the results of research giving a large vision for the facts and happenings of the university teaching and about the importance that the academics had and still haven in story of the education, thus, they cannot be silenced in the history of Brazilian education.